The Criteria of Site Selection for Farmers’ Markets - Dorottya Szabó (DETUROPE)
Over the past few years the number of farmers’ markets in Hungary has considerably grown what was induced both by the growing demand and the occurrence of facilitated authorization requirements. At the same time according both to international and Hungarian experience the dynamic increase in the number of farmers’ markets has occurred together with a notably high closure rate. Markets having characteristically small number of vendors, narrow variety of products, unsatisfactory organizing capacity and experience, as well as markets operating at an inadequate site were generally closed during the first four years. The present study aims to describe a factor system relevant for the site selection of markets that was made measurable by the adaption of a multi dimension criteria system developed in the United States of America for domestic circumstances. The final aim is the development of a toolkit that can help in the evaluation by this in the comparison of the existing and potential markets sites in Hungary.